Theoretical Study of Concepts and Forms of Social Structure - Misbakhul Anam; Arditya Prayogi (Cognitionis Civitatis et Politicae, 2024)
In living in society, every human being must have their own role and status. Differences in roles and status in humans show that there is a social structure within them. This article aims to explain the basic concepts and forms in a society's social structure. This article was prepared using a qualitative approach supported by literature study methods and analyzed using content analysis. From the results of the study, it is clear that social structure is a system that has a reciprocal relationship with individuals so that changes in social structure can be caused by individual changes in society, and individual changes can be caused by changes in social structure and the formation of these systems in vertical and horizontal formats.